ENCOURAGING READING INTEREST USING PICTURE STORY BOOKS TO YOUNG LEARNERS - Pipit Ertika Daristin; Maskhurin Fajarina (Jurnal Bastra (Bahasa dan Sastra), 2022)
Reading is one of the fundamental skills needed to improve language skills and global knowledge. The key to increasing students' reading interest is to get them used to read from an early age. The purpose of this study was to describe the use of picture story books to increase students' reading interest in literacy activities and to find out teacher and student responses to it. This research is a qualitative descriptive study that includes teachers and 32 first-grade students in an elementary school in Trenggalek as research subjects. Based on the study's results, the use of picture story books in literacy activities was carried out in six steps with a different story at each meeting. Furthermore, teachers and students gave positive responses about it. Teachers agree that learning with picture story books can increase students' reading interest because pictures can help them understand the meaning of unknown words. Also, the use of picture story books can be an illustration to guide students in understanding the storyline and help develop students' cognitive aspects in critical thinking, as well as creating a sense of pleasure and enthusiasm during the reading process.